Carceral space, prisoners and animals - Morin, Karen M. (Routledge human-animal studies series, 2018)
"Carceral Spaces and Animals develops a framework for exploring embodied, geographical, legal, and ethical resonances across human and nonhuman carceral spaces. This book examines the close linkages that can be found across prisoner and animal carcerality and captivity, focusing on their corresponding and parallel disciplinary regimes and structures of violence. Case studies juxtapose four main types of institutions: death row and slaughterhouse; laboratory testing on incarcerated humans and animals, solitary confinement, and sites of exploited labor. The shared structural conditions and inequalities that span species boundaries at these sites are explored theoretically and conceptually, looking at emotional and psychological strain, the geographies of these carceral spaces, legal mechanisms (or the lack of) and the ethical questions that arise when we consider the potential for these sites to become locations of genocide and/or extinction of particular populations"--